Simulation of dislocation evolution in microparticle impacts over a wide range of impact velocities. (November 2022) - Larkin, Kevin; Hunter, Abigail; Buechler, Miles
Abstract: The dynamic loading environment created by high velocity microparticle impacts is very difficult to model. The extremely high strain rates, large deformations, and high temperatures affect the flow stress of the material in ways that standard flow stress models cannot capture. Plastic deformation and strain hardening in metals is controlled by the motion of dislocations. Dislocations can be nucleated, stored as forest dislocations, or be annihilated as loading progresses. A comprehensive accounting of dislocation density change is needed to accurately describe rate and temperature dependent dislocation glide and evolution across the wide rage of loading conditions present in microparticle impact problems. Therefore, we implement and apply a newly proposed flow stress model (Hunter and Preston, 2015, 2022) that is then coupled with mobile and immobile dislocation density evolution equations. This model is implemented in Los Alamos National Laboratory's hydrodynamics code, FLAG, to model copper-on-copper microparticle impacts. This new strength model allows for accurate simulation of particle rebound and flattening across a wide range of impact velocities. Graphical abstract: Highlights: Rate-dependent flow stress model based on dislocation dynamics. Simulation of deformation in high velocity microparticle impacts. Dislocation density evolution in highly deformed copper particles.